Comparative fitness analysis of D-cycloserine resistant mutants reveals both fitness-neutral and high-fitness cost genotypes - Dimitrios Evangelopoulos (Nature Portfolio, 2019)
D-cycloserine (DCS) has been used for decades to treat Mycobacterium tuberculosis (Mtb) but resistance is rarely observed in clinical isolates. Here, the authors report ultra-low rate of emergence of resistance mutations as the underlying mechanism of DCS resistance evasion in Mtb.